1999
DOI: 10.1111/j.1600-0447.1999.tb07229.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory levels of catecholamines, serotonin and lipids in attention deficit hyperactivity diiorder

Abstract: Attention deficit hyperactivity disorder (ADHD) may be associated with a dysregulation of the catecholaminergic and serotonergic systems. Furthermore, ADHD is frequently complicated by aggressive impulsive behaviour, which is suggested to be related to low serum cholesterol levels. We examined the relationship between blood serotonin, norepinephrine, dopa and lipid levels and the degree of hyperactivity, impulsiveness, lack of concentration, and aggressiveness in boys with ADHD of low and high severity as dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 19 publications
2
51
0
5
Order By: Relevance
“…17,18 Altered cerebrospinal fluid concentrations of 5-hydroxyindoleacetic acid, a serotoninergic metabolite, are consistently associated with hyperactivity, aggression and impulsive behavior, common characteristics in ADHD. [19][20][21] In addition, it has been reported that tryptophan depletion, the essential amino acid for brain serotonin synthesis, impairs learning and memory in healthy controls. 22 Pharmacological studies have also provided insight into the role of serotonin in ADHD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Altered cerebrospinal fluid concentrations of 5-hydroxyindoleacetic acid, a serotoninergic metabolite, are consistently associated with hyperactivity, aggression and impulsive behavior, common characteristics in ADHD. [19][20][21] In addition, it has been reported that tryptophan depletion, the essential amino acid for brain serotonin synthesis, impairs learning and memory in healthy controls. 22 Pharmacological studies have also provided insight into the role of serotonin in ADHD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These results have been further supported by a recent study that also found a tendency towards low platelet serotonin in a sample of children with severe ADHD. 7 Additional support for a serotonin hypothesis is demonstrated by the moderate efficacy of several serotonin enhancing agents in the treatment of ADHD including selective serotonin reuptake inhibitors (SSRIs) 8 and certain selective monoamine oxidase inhibitors. 9 Several lines of evidence have indicated abnormal serotonergic function in children with disruptive behaviour disorders (ADHD, ODD, CD) who display marked problems with hyperactivity, impulsivity, and aggression.…”
Section: Using the Transmission Disequilibrium Test (Tdt)mentioning
confidence: 99%
“…The serotonin transporter gene has been proposed as a candidate gene for ADHD and may be involved in the aetiology of impulsivity (Halperin et al 1997;Spivak et al 1999;Stein et al 1993). One of the most studied polymorphisms of this gene (the 5HTTLPR) is located in the promoter region of this gene.…”
Section: Geneticsmentioning
confidence: 99%